Communities of practice for international students: An exploration of the role of Peer Assisted Study Sessions in supporting transition and learning in higher education - Lucy Chilvers (Association for Learning Development in Higher Education (ALDinHE), 2016)
There is growing interest in understanding how international students can best be enabled to adjust to, participate in and learn within Higher Education (HE). This paper explores literature and examines findings from exploratory interviews in a UK institution in order to investigate the contribution the Peer Assisted Study Sessions (PASS) scheme makes to this process.